(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article reviews issues that examine the concept known as "Alpha engendering", whose main characteristic is the valorization of technological autonomy in the contemporary educational context. The approach is based on dynamic pedagogical practices that reconcile the valorization of the collective with respect for individuality, promoting an agile and innovative educational process with the potential to stand out historically. Gamification is understood as a promising resource - almost a "savior" - in facing the challenges imposed by distance education. The pedagogical practice is analyzed based on the incorporation of playful elements, such as digital games, which stimulate critical thinking, favor cognitive development and reposition the student as the protagonist of his/her learning process, that is, as the author of knowledge. The article, in addition to gamification, addresses the use of active methodologies, such as project-based learning, hybrid teaching and the flipped (or reversed) classroom, which break with traditional teaching models and seek greater student engagement. It also discusses e-learning, a form of teaching mediated by digital technologies and social networks, which expands the possibilities of access to knowledge, but which also reveals contradictions, such as the false sense of balance promoted by digital platforms, while at the same time accentuating social inequalities. The article is based on a literature review and an interview published with Professor Nelson Pretto, recognized for his defense of critical, militant and transformative education. We analyze the author’s emphasis on the role of digitalization in the educational process, focusing on the importance of democratizing communication, the use of free software in the school environment and the discussion about internet ownership, often concentrated in the hands of large corporations. The article proposes a deep reflection on the paths of education in the digital age, considering both the potential and the risks of technologies, especially with regard to autonomy, inclusion and social justice in the educational environment.